2000
DOI: 10.1111/j.1749-6632.2000.tb07043.x
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan (Hycamptin) and Topotecan‐Containing Regimens in the Treatment of Hematologic Malignancies

Abstract: Single-agent topotecan is an active drug in chemotherapy-naive MDS and CMML and, to a lesser degree, in refractory/relapsed acute leukemias, low-/intermediate-grade lymphoma, and myeloma. Its combination with cytosine arabinoside induces complete remissions in high-risk MDS/CMML. A triplecombination regimen of cyclophosphamide, cytosine arabinoside, and topotecan (CAT) was extensively tested in refractory/relapsed as well as in untreated AML. By proving effective in inducing complete remission in newly diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Other investigators have reported the efficacy of topotecan in the treatment of lymphoma and myelodysplastic syndromes (16). In these lymphoma studies, investigators used daily 30-minute infusion of topotecan alone or with etoposide or paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported the efficacy of topotecan in the treatment of lymphoma and myelodysplastic syndromes (16). In these lymphoma studies, investigators used daily 30-minute infusion of topotecan alone or with etoposide or paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Phase II studies in adults based on prolonged exposure (primarily daily × 5 administered every 3 weeks) achieved encouraging results for the treatment of ovarian carcinoma [25,26] and small cell lung cancer [27,28] and in myelodysplastic syndrome and chronic myelomonocytic leukemia [29]. Phase II studies in children confirmed the achievement of improved outcomes when topotecan was administered for 5 consecutive days both in neuroblastoma and rhabdomyosarcoma [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Novel agents are required to improve the prognosis of patients with myeloid leukemias 1. The topoisomerase I (topo I) inhibitor topotecan has demonstrated significant activity, both as a single agent and in combinations, in patients with acute myeloid leukemia (AML) or myelodysplastic syndromes (MDS) 1–10. In single‐agent studies, other topo I inhibitors, including 9‐aminocamptothecin and DX‐8951f, also have demonstrated antileukemia activity in both severe combined immunodeficient (SCID) mouse models of human leukemia and in Phase I studies 11–14.…”
mentioning
confidence: 99%